Assessment of endocrine disruptor effects of levonorgestrel and its photoproducts : Environmental implications of released fractions after their photocatalytic removal - Narváez Valderrama, Jhon Fredy; Grant, Hannah; Gil, Vanessa Correa; Porras López, Jazmín; Bueno Sanchez, Julio Cesar; Ocampo Duque, Luz Fanny; Sossa, Ramiro Ríos; Quintana Castillo, Juan Carlos (Elsevier BV, 2019)
The presence of levonorgestrel (LNG) in water bodies via direct discharge and human excretion has been reported worldwide, but its effects on the reproduction of aquatic species and humans are still unknown. Owing to its recalcitrant properties, LNG is not completely removed during wastewater treatment plants, and many species may be exposed to low traces of this compound from discharged effluents. Thus, in this study, a photocatalytic process for removing LNG along with screening of endocrine disruptor effects for risk assessment was applied. Although the removal rate of LNG by ultraviolet C (UV-C) radiation was >90%, reproductive toxicity testing using the BeWo cell line exposed to LNG and its degraded fraction showed the reduced production of basal human chorionic gonadotropin hormone (β-hCG) by more than 73%, from 8.90 mIU mL−1 to <2.39 mIU mL−1, with both LNG and the degraded fraction. β-hCG hormone has been implicated in the viability of trophoblastic cells during the first trimester of pregnancy; therefore, degraded fractions and waterborne LNG may affect reproduction in some aquatic species and humans with low level of exposure.
Keywords: Endocrine disruptor; Photocatalytic Degradation; BeWo Cell Line; β-hCG Hormone; Photocatalytic Removal; Levonorgestrel; Aguas residuales; Salud publica